2018
DOI: 10.7759/cureus.3048
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Effect of Comorbid Cystic Fibrosis and Attention Deficit Hyperactivity Disorders on Hospitalizations: A Retrospective Analysis

Abstract: Introduction: The prevalence of attention-deficit/hyperactivity disorder (ADHD) in pediatric cystic fibrosis (CF) patients is comparable to the general population, but the effects of ADHD on CF treatment and the outcomes have been minimally investigated.Methods: Two cohorts were retrospectively reviewed, pediatric patients with comorbid CF/ADHD and patients with CF only. Each patient with CF/ADHD was age and sex-matched to a CF-only patient based on their most recent pulmonary office visit. Each patient was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…Our review demonstrated that measures used to aid diagnosis of ADHD or associated symptoms (i.e., attention difficulties or executive functioning) were inconsistent across studies. A variety of approaches to symptom assessment was employed including chart review to confirm diagnosis, self-report measures (e.g., ADHD-RS, ADHD Self-Report Scale v.1.1, BASC-II, BDEFS-CA), 12,18,21 caregiver report measures (e.g., BASC-II, BRIEF), 16,22 structured diagnostic interviews (e.g., KSADS), 17 and direct neurocognitive or computer measures of attention (e.g., TEA-Ch, D-KEFSd2 test, CPT). 19,23 While all studies included used psychometrically validated measures, the inconsistency in use of measures across studies makes it difficult to compare results across studies.…”
Section: Discussionmentioning
confidence: 99%
“…Our review demonstrated that measures used to aid diagnosis of ADHD or associated symptoms (i.e., attention difficulties or executive functioning) were inconsistent across studies. A variety of approaches to symptom assessment was employed including chart review to confirm diagnosis, self-report measures (e.g., ADHD-RS, ADHD Self-Report Scale v.1.1, BASC-II, BDEFS-CA), 12,18,21 caregiver report measures (e.g., BASC-II, BRIEF), 16,22 structured diagnostic interviews (e.g., KSADS), 17 and direct neurocognitive or computer measures of attention (e.g., TEA-Ch, D-KEFSd2 test, CPT). 19,23 While all studies included used psychometrically validated measures, the inconsistency in use of measures across studies makes it difficult to compare results across studies.…”
Section: Discussionmentioning
confidence: 99%
“…While few studies have focused specifically on preadolescent children with CF, another small Turkish cohort found ADHD diagnosed by KSADS in 30% of children with CF ages 8 to 11 years and 10% of healthy controls ( P = .235) 13 . Male children with CF are two to three times more likely to be diagnosed with ADHD 21,87,88 ; disruptive behaviors may be less common in girls than in boys with ADHD, resulting in under‐referral despite equivalent impairment 83 . Although ADHD prevalence among adults with CF is three to four times that expected in the general population, no gender imbalance has emerged in this age group 21,22 .…”
Section: Developmental Disordersmentioning
confidence: 99%
“…Impairment in EF is a hallmark of attention‐deficit/hyperactivity disorder (ADHD), and emerging research indicates higher rates of self‐reported ADHD symptoms in adults and children with CF compared to the general population 15,16 . One study reporting on the impact of comorbid ADHD on CF in a small pediatric sample found minimal differences, with better lung function in youth with CF and ADHD compared to youth with CF alone 17 . Another study found that youth with ADHD and CF had more recent dornase alfa (a routine nebulized medication) use compared to youth with CF alone 18 .…”
Section: Introductionmentioning
confidence: 99%
“…15,16 One study reporting on the impact of comorbid ADHD on CF in a small pediatric sample found minimal differences, with better lung function in youth with CF and ADHD compared to youth with CF alone. 17 Another study found that youth with ADHD and CF had more recent dornase alfa (a routine nebulized medication) use compared to youth with CF alone. 18 Neither of the above ADHD-focused studies included details on specific ADHD symptoms or measures of executive functioning.…”
Section: Introductionmentioning
confidence: 99%